Spatial-temporal differentiation characteristics of the coupling of urban resilience and green development efficiency in resource-based cities(资源型城市韧性水平与绿色发展效率耦合的时空分异特征) - 张赛茵(ZHANG Saiyin); 王启翔(WANG Qixiang); 袁佳欣(YUAN Jiaxin); 王金伟(WANG Jinwei) (Zhejiang Daxue xuebao. Lixue ban)
Yellow River Basin is an important industrial belt for energy development in China with a large number of resource-based cities. However, due to the large-scale energy development and coal mining, Yellow River Basin has encountered the problems of fragile ecological environment, unreasonable resource allocation and low development quality. Nowadays, urban resilience construction and green development have become an important direction for transformation and development of resource-based cities in Yellow River Basin as the research object, this paper constructs the coupling mechanism between urban resilience and green development efficiency, and quantitatively measured the spatio-temporal pattern of coupling coordination between resilience and green development efficiency of 40 resource-based cities from 2010 to 2019 by using the physical coupling model. Based on the stochastic effects panel Tobit model, the coupling factors of resilience and green development efficiency of resource-based cities in Yellow River Basin are studied. The results show that: (1) The resilience construction of resource-based cities in Yellow River Basin has achieved remarkable progress with a steady growth trend. The green development efficiency reveals a "W" shaped fluctuation growth trend over time, and the overall growth efficiency is not significant. (2) The mean value of the system coupling degree between them fluctuates within the range of [0.7, 0.8], presenting a high coupling relationship. In addition, the degree of coupling coordination shows a trend of steady improvement over time. (3) The spatial heterogeneity of urban resilience, green development efficiency, and their coupling degree and coupling coordination degree are consistent, that is, resource-based cities in the middle and lower reaches are stronger than those in the upper reaches. (4) Government capacity, education input and population size have significant spatial differences on the impact of coupled coordinated development, while infrastructure, industrial structure and environmental regulation have spatial homogeneity. In the context of the national strategy of accelerating green transformation of resource-based cities, this study is of certain guiding significance for promoting resource-based cities to get rid of dependence on regional economic development path and high-quality development through resilience governance.(城市韧性建设和绿色发展已成为资源型城市转型发展的重要方向。以黄河流域资源型城市为研究对象，通过构建城市韧性水平与绿色发展效率的耦合机理，利用物理学耦合模型，定量测度了2009—2019年40个资源型城市的韧性水平与绿色发展效率耦合协调的时空格局；通过构建随机效应面板Tobit模型，探究黄河流域资源型城市韧性水平与绿色发展效率耦合的影响因素。研究发现：（1）黄河流域资源型城市韧性建设成效显著，呈稳步增长态势；绿色发展效率随时间呈“W”形波动增长态势，但总体增长效率不显著。（2）两者耦合度均值在［0.7，0.8］内波动，呈现较高的耦合关系；耦合协调度随时间呈稳步提升态势，从“濒临失调阶段”逐步过渡到“良好协调阶段”。（3）城市韧性水平、绿色发展效率，以及两者间的耦合度和耦合协调度的空间异质性具有一致性，即中下游资源型城市强于上游。（4）政府能力、教育投入和人口规模对耦合协调度的影响存在较显著的空间异质性，而基础设施、产业结构和环境规制的影响具有空间同质性。)